Fourth Contribution on Late Eocene Amber Silken Fungus Beetles: a New Baltic Amber Species of Atomaria (Coleoptera, Clavicornia, Cryptophagidae) - Lyubarsky, G.Yu.; Perkovsky, E.E. (Вестник зоологии, 2013)
Atomaria gedanicola Lyubarsky et Perkovsky, sp. n., a new cryptophagid species from Baltic amber is described. The new species is the first recorded Eocene Atomariinae. The new species is similar to A. fuscipes Gyllenhal. It differs from the latter in having pronotum flat, posterior angles of pronotum obtuse, and antenna short. The record of A. gedanicola syninclused with Ceratopogon biting midge supports the Late Eocene age of the Baltic amber, for the Holarctic affinities of both taxa are incompatible with the paratropical climate characteristic of the Mid-European Middle Eocene. Описан новый вид криптофагид из балтийского янтаря — Atomaria gedanicola Lyubarsky et Perkovsky, sp. n. Это первый эоценовый представитель Atomariinae. Новый вид сходен с A. fuscipes Gyllenhal, от которого отличается плоским пронотумом с тупыми задними углами и короткими антеннами. Нахождение A. gedanicola в сининклюзе с мокрецом Ceratopogon указывает на позднеэоценовый возраст балтийского янтаря, так как голарктическая приуроченность обоих таксонов несовместима с паратропическим климатом среднего эоцена Средней Европы.